Developing a health promoting occupational therapy program for community living older people : experiences from a European project group - Daniëls, Ramon, ....-; Mountain, Gail, ....- (Amsterdam : Enothe, 2008)
1. Introduction 2. The Lifestyle Redesign program as a starting point 3. Models for designing and implementing health promoting programs 4. Empirical underpinnings of occupational based health promoting programs 5. Project implementation in five European Countries
Keywords: Gezondheidsvoorlichting -- Ouderen